2022
DOI: 10.1088/2040-8986/ac461c
|View full text |Cite
|
Sign up to set email alerts
|

Quantum optical analysis of squeezed state of light through dispersive non-Hermitian optical bilayers

Abstract: We investigate the propagation of a normally incident squeezed coherent state of light through dispersive non-Hermitian optical bilayers, particularly at a frequency that the bilayers hold parity-time (PT) symmetry. To check the realization of PT-symmetry in quantum optics, we reveal how dispersion and loss/gain-induced noises and thermal effects in such bilayers can affect quantum features of the incident light, such as squeezing and sub-Poissonian statistics. The numerical results show thermally-induced nois… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…During its life as a preprint [ 73 ], applications of the formalism and results as developed in an earlier version of this paper have already been applied in several works, including Refs. [ 74 , 75 ]. These concentrate on the realization of -symmetric optical systems and the propagation of quantum states of light through them.…”
Section: Introductionmentioning
confidence: 99%
“…During its life as a preprint [ 73 ], applications of the formalism and results as developed in an earlier version of this paper have already been applied in several works, including Refs. [ 74 , 75 ]. These concentrate on the realization of -symmetric optical systems and the propagation of quantum states of light through them.…”
Section: Introductionmentioning
confidence: 99%
“…In quantum optics, optical loss and hence the nonhermiticity are detrimental, and therefore researchers have been working hard trying to avoid it. However, very recent studies have shown that non-Hermitian optical systems could be exploited for exotic manipulation of quantum optical states, such as one-sided quantum interference and the insensitivity of the quantum state of light to thermally induce noise in certain non-Hermitian optical systems . These studies open up new possibilities for non-Hermitian optical metasurfaces for potential applications in quantum state preparation and information processing.…”
Section: Discussionmentioning
confidence: 99%
“…In what follows, we use the above parameters to numerically analyze the structure under study. We know that the thermal noise effect at room temperature and zero Kelvin, for the given incident frequency, are both insignificant [15]. Henceforward, we consider keeping the gain and loss layers at 0 K. In this section, we study how the second-order correlation function [21] (…”
Section: The Second-order Coherencementioning
confidence: 99%
“…ˆR R FF  is the average flux of the noise photons, which is given by (B7) in [15] for the exact multilayer theory. The dependency of the second-order coherence (11) on the dimensionless time delay, τ ωPT, is plotted in Fig.…”
Section: A Number Statementioning
confidence: 99%
See 1 more Smart Citation